O gatunkach przestrzeni - Rapior, Waldemar (Człowiek i Społeczeństwo, 2012)
This article present four species of space, species that express, through the material culture, different forms of gathering: the crowd, the lonely crowd, community, co-operation and the way that people experience closeness and togetherness. The four species of space are: the space of mass, of individualism, of tribe and, last but not least, the space of solidarity. We can think of the species of space as a metaphor which we can use to describe the material realm, but also as a tool for changing the world and creating social change. We live together. However, we are not only tied up with longterm relationships but with weak ties. The latter are based on the materiality. I suggest that space is not purely physical (size, shape, weight) but it is rather the script, the specie which, in the dynamic evolutionary process, adapts to the historical and social circumstances.